TWO NEW HOSTS FOR GORYTHOCEPHALUS ELONGORCHIS (ACANTHOCEPHALA: NEOECHINORHYNCHIDAE), IN DEKEISERIA AMAZONICA AND HYPOSTOMUS OCULEUS (SILURIFORMES: LORICARIIDAE) FROM THE BRAZILIAN AMAZON - Silva Jtineant, Amanda Karen (2022)
Specimens of Dekeiseria amazonica Rapp Py-Daniel, 1985 and Hypostomus oculeus (Fowler, 1943) captured from July 2015 to December 2016, in the Catalão Lake complex, Iranduba, Amazonas, were studied. The specimens of D. amazonica measured 12 – 16.5 (13.70 ± 1.33) and weight (g) 29 – 59 (40.85 ± 9.78) and H. oculeus 12 – 21 (15.80 ± 2.13) and weight (g) 75 - 125.40 (101.11 ± 14.28). Both species were parasitized by the acanthocephalan Gorytocephalus elongorchis Thatcher, 1979 (Neoechinorhynchidae), parasitizing the intestine, with a prevalence of 55% and abundance of 18.  The intensity ranged from 1 to 3 parasites and the average intensity was 1.63 parasites per fish for D. amazonica, and prevalence 59.25%, abundance 29. The intensity of 1 to 4, mean intensity 1.81 for H. oculeus. Two new hosts for G. elongorchis are recorded and their specificity for fish of the Loricariidae is highlighted. This is the first record of G. elongorchis parasitizing D. amazonica and H. oculeus.